The great Indian phone book : how the cheap cell phone changes business, politics, and daily life - Doron, Assa (Harvard University Press, 2013)
In 2001, India had 4 million cell phone subscribers. Ten years later, that number had exploded to more than 750 million. Over just a decade, the mobile phone was transformed from a rare and unwieldy instrument to a palm-sized, affordable staple, taken for granted by poor fishermen in Kerala and affluent entrepreneurs in Mumbai alike. The Great Indian Phone Book investigates the social revolution ignited by what may be the most significant communications device in history, one which has disrupted more people and relationships than the printing press, wristwatch, automobile, or railways, though it has qualities of all four.